User needs analysis for developing plant monitoring information system: enhancing agricultural efficiency and productivity - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This research explores users' needs and barriers in developing a plant monitoring information system to enhance agricultural efficiency. Through a qualitative approach, the needs of farmers and agricultural managers and challenges in technology adoption are analyzed. The findings emphasize the importance of a user-friendly system relevant to its users. By gathering data through interviews, observations, and document studies, desired features for the plant monitoring information system are identified. As a result, solutions are recommended to improve crop management efficiency and support sustainable farming practices. This research contributes to understanding user needs in the context of agricultural technology development, hoping to enhance overall productivity and sustainability in the agricultural sector.